1988
DOI: 10.1111/j.1467-8306.1988.tb00238.x
|View full text |Cite
|
Sign up to set email alerts
|

On Education and Geographers: The Role of Cognitive Developmental Theory in Geographic Education

Abstract: The current focus on geographic ignorance within the discipline and within the mass media offers another opportunity t o reform the teaching of geography at all grade levels. Previous reforms have met with little success. We argue that current efforts will succeed only if we integrate ideas from geography, child development, and education. Programs of geographic education must link geographic content with an understanding of the nature of the learner and with the expectations and knowledge of the teacher. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
12

Year Published

1998
1998
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 21 publications
2
38
0
12
Order By: Relevance
“…We attempted to manipulate the initial portions of routes by inserting regions and boundaries onto the map. Previous work (e.g., Bailenson et aI., 1998;Downs, Liben, & Daggs, 1988;Sadalla et aI., 1980) has shown that people tend to make route decisions on a region-by-region basis when a map is segmented into a number ofbordering areas. That is, people focus on route choices within a given region and follow the selected route until they reach the next region, where they repeat the decision-making process.…”
Section: Biasrightmentioning
confidence: 99%
“…We attempted to manipulate the initial portions of routes by inserting regions and boundaries onto the map. Previous work (e.g., Bailenson et aI., 1998;Downs, Liben, & Daggs, 1988;Sadalla et aI., 1980) has shown that people tend to make route decisions on a region-by-region basis when a map is segmented into a number ofbordering areas. That is, people focus on route choices within a given region and follow the selected route until they reach the next region, where they repeat the decision-making process.…”
Section: Biasrightmentioning
confidence: 99%
“…Modellen bygger på tidligere erfaringer og forskning rundt barns forutsetninger for å lese et kart (Bjerva, et al, 2008;Downs, et al, 1988;Graesli, 2007;Sigurjónsson, 2007). Kartstigen inneholder fem nivåer, og intensjonen er at barnet mestrer hvert nivå før det fortsetter videre til det neste.…”
Section: Mål For Studienunclassified
“…Kartet vil for eksempel vise litt av veggene i en bygning, og ikke bare formen på taket. Tidligere forskning antyder at det er enklere for barn å se et område i perspektiv, enn å forestille seg hvordan det vil se ut ovenfra (Downs, et al, 1988;Robison & Spodek, 1965). Slike skråkart kan både vaere tegning eller foto.…”
Section: Mål For Studienunclassified
See 2 more Smart Citations